Whole Genome Sequencing Based Surveillance of L. monocytogenes for Early Detection and Investigations of Listeriosis Outbreaks - Pietzka, Ariane; Allerberger, Franz; Murer, Andrea; Lennkh, Anna; Stöger, Anna; Cabal Rosel, Adriana; Huhulescu, Steliana; Maritschnik, Sabine; Springer, Burkhard; Lepuschitz, Sarah; Ruppitsch, Werner; Schmid, Daniela (Frontiers in Public Health, 2019)
In Austria, all laboratories are legally obligated to forward human and food/food-associated L. monocytogenes isolates to the National Reference Laboratory/Center (NRL) for Listeria. Two invasive human isolates of L. monocytogenes serotype 1/2a of the same pulsed-field gel electrophoresis (PFGE) pattern, previously unknown in Austria, were noticed for the first time in January 2016. Five further human isolates, obtained from patients with invasive listeriosis between April 2016 and September 2017, showed this PFGE pattern. In Austria the NRL started to use whole-genome sequencing (WGS) based typing in 2016, using a core genome MLST (cgMLST) scheme developed by Ruppitsch et al. 2015, which contains 1701 target genes. Sequence data are submitted to a publicly available nomenclature server (Ridom GmbH, Münster, Germany) for allocation of the core genome complex type (CT). The seven invasive human isolates differed from each other with zero to two alleles and were allocated to CT1234 (declared as outbreak strain). Among the Austrian strain collection of about 6,000 cgMLST-characterized non-human isolates (i.e. food/food-associated isolates) 90 isolates shared CT1234. Out of these, 83 isolates were traced back to one meat processing-company. They differed from the outbreak strain by up to seven alleles; one isolate originated from the company’s industrial slicer. The remaining seven CT1234-isolates were obtained from food products of four other companies (five fish-products, one ready-to-eat dumpling and one deer-meat) and differed from the outbreak strain by six to eleven alleles. The outbreak described shows the considerable potential of WGS to identify the source of a listeriosis outbreak. Compared to PFGE analysis, WGS-based typing has higher discriminatory power, yields better data accuracy, and allows higher laboratory through-put at lower cost. Utilization of WGS-based typing results of human and food/food-associated L. monocytogenes isolates by appropriate public health analysts and epidemiologists is indispensable to support a successful outbreak investigation.